2018
DOI: 10.1080/10888705.2018.1456339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental enrichment on activity and lameness in commercial broiler production

Abstract: The aim of this pilot study was to investigate the effects of commercially applied environmental enrichments on behavior and lameness in broilers. Two consecutive flocks of broilers were observed at 16 days and 30 days of age to investigate differences between enriched (peat, bales of lucerne hay, and elevated platforms) and control birds with regards to behavioral activities and lameness. More running (p < .001), worm running (p = .006), play fighting (p = .015), dust bathing (p = .009), and ground pecking wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 15 publications
5
87
1
2
Order By: Relevance
“…In the Undisturbed patches, a reduction in Play, Exploration, Comfort behaviour and Any Positive Behaviour counts was observed from the first to last Production Stages. Lower Play in the final production stage is consistent with Vasdal et al 's 41 finding of less play at 30 days compared to 16 days, and the observed reduction in Exploratory behaviour with increasing age is consistent with Bizeray et al 38 . For the Disturbed patches, less Play was recorded in Production Stage 1 than when the birds were older.…”
Section: Discussionsupporting
confidence: 86%
“…In the Undisturbed patches, a reduction in Play, Exploration, Comfort behaviour and Any Positive Behaviour counts was observed from the first to last Production Stages. Lower Play in the final production stage is consistent with Vasdal et al 's 41 finding of less play at 30 days compared to 16 days, and the observed reduction in Exploratory behaviour with increasing age is consistent with Bizeray et al 38 . For the Disturbed patches, less Play was recorded in Production Stage 1 than when the birds were older.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, scientific knowledge is unclear about effects of these objects on leg/foot health and on activity (Riber, et al, 2018). Recently, a few studies have reported positive effects of combining bales of straw or lucerne hay with other enrichment on reducing leg/foot problems in fastgrowing broilers (Baxter, et al, 2018b;Vasdal, et al, 2019), and in slow-growing broilers, bales of straw have been found to increase activity levels (Bergmann, et al, 2017), whereas in fast-growing broilers some studies show an increased activity level, and others do not.…”
Section: Summing Up On Point-source Enrichmentsmentioning
confidence: 99%
“…The provision of a more diverse environment, with for instance platforms combined with other type of enrichment (e.g. bales), may aid to improve leg health (Baxter, et al, 2018b;Vasdal, et al, 2019) and reduce smothering and injuries at catching by reducing fearfulness already during the production cycle.…”
Section: Environmental Enrichmentmentioning
confidence: 99%
“…Environment enrichment는 동물관리의 핵심으로 동물의 행동 욕구가 충족될 수 있도록 동물에게 제공하는 항목을 말하며 (Coleman et al, 2013) (Riber et al, 2018). 농장에서 복 지 환경을 제공하면 생산성에는 영향이 없지만 (Aksit et al, 2017), 닭의 복지 지표 향상 (Vasdal et al, 2019), 면역능 향 상 (Mohamed et al, 2014;Matur et al, 2016), 그리고 닭고기 내 병원성 미생물 오염수준이 감소 (Iannetti et al, 2020)한다 고 보고된 바 있다. 이와 반대로 복지가 향상된 환경에서 자 란 육계에서 생산성 감소, 폐사율 증가 및 가슴육의 전단력 (shear force)이 증가하였다는 결과도 보고된 바 있다 (Zhao et al, 2014).…”
unclassified